Pengukuran Kinerja Operasional Perusahaan Meubel Berdasarkan Konsep Green Manufacturing untuk Mewujudkan Keberlanjutan Proses - Evi Yuliawati; Septian Dwi Prasetyo (Universitas Indraprasta PGRI Jakarta, 2023)
The rapid development of the industrial sector encourages the emergence of environmental issues, especially the global warming. The phenomenon occurs because of many factors. The most common factor is the manufacturing industry which mostly utilizes natural resources and non-renewable energy. In an observation made on Meuble Company XXX, there are flaws in waste management during its production process. Scattered wooden wastes are visible in the production area and there are no major attempts to reduce the production process’ impact on surrounding air pollution. Based on the observation, this research attempts to determine Meuble Company XXX’s operational capability based on indicators of Green Manufacturing in accordance with The Organization for Economic Co-operation and Development’s (OECD). The research result indicates two indicators, namely waste intensity and air pollution intensity need further evaluation that the company can apply the green manufacturing concept better. The result also shows there are 6 indicators with null score, meaning the company does not use natural resources or non-renewable energy during those processes and there is no negative impact on the environmentt. Based on results, it can be concluded that the operational performance of Company Meuble XXX on Green Manufacturing is in Advance category.